(untitled) (Hekima Review, 2013)
Discuss three specific languages that I will call scientific, metaphysical and religious. They all are part of the natural languages. Scientific language conveys public information and meaning. Metaphysical language conveys information and meaning that goes beyond scientific knowledge. Finally, religious language, especially in the revealed religions and in the Christianity, is characterized by the initiative that God takes in communication.I study interrelations between the languages of science, that I call languages of sign and the languages of metaphysics and religion, that I call languages of symbol. The interrelation between these types of language will help us better understand the current cultural problems of the relation between Science and Religion. At the beginning and end of the paper I quote the prologue of the Gospel of John to indicate the uniting power of the various languages that is present in the Christian Word